Diagnosis of Stage II Rheumatoid Arthritis through Functional Evaluation of Wrist and Hand among Adult Females - Sana Saleem; Maleeha Fuad; Samreen Sadiq; Hafiz Muhammad Asim (ziauddin University, 2020)
Background: Rheumatoid arthritis (RA) is a commonly prevailing disease among women. Disease progression deformities such as ulnar and radial shift of the wrist, Boutonnière, swan neck deformity and mallet finger become evident, which results in marked limitation of hand function. Patients usually lose the ability to hold, grasp and pinch thus activities of daily living are compromised. This study aimed to diagnose stage II Rheumatoid Arthritis through assessing the limitations of hand functions in adult females. Methods: A sample of 37 adult females with Stage II RA presenting to the rheumatology department of National hospital, Lahore and Combined Military Hospital, Lahore were recruited in the study. Patients with clinically diagnosed Stage II RA presenting with pain and dysfunction of the hands and wrist joints were included. Patients with any traumatic condition or any other bone disease that limits hand function were excluded from the study. The scale used for the assessment was Patient Rated Wrist/Hand Evaluation (PRWHE) with the reliability of >0.75 and validity of 0.7. Results: In a sample of adult women with a mean age of 42, 39% reported moderate pain and 61% had severe pain whereas the functional limitations was reported to be moderate in 47.3% while 52.7% had severe limitation of hand function. These results prove that there is a negative impact of hand malformations on hand function. Conclusion: The adult females with stage II Rheumatoid Arthritis had severely limited hand function. The functional limitations of hand were increased with disease progression especially in adult females.